Sex, Age and Stature Affects Neck Biomechanical Responses in Frontal and Rear Impacts Assessed Using Finite Element Head and Neck Models - Corrales, M. A; Cronin, D. S (Frontiers in Bioengineering and Biotechnology, 2021)
The increased incidence of injury demonstrated in epidemiological data for the elderly population, and females compared to males, has not been fully understood in the context of the biomechanical response to impact. A contributing factor to these differences in injury risk could be the variation in geometry between young and aged persons and between males and females. In this study, a new methodology, coupling a CAD and a repositioning software, was developed to reposture existing FE neck while retaining a high level of mesh quality. A 5th percentile female aged neck model (F0575YO) and a 50th percentile male aged neck model (M5075YO) were developed from existing young (F0526YO and M5026YO) neck models (GHBMC v5.1). The aged neck models included an increased cervical lordosis and an increase in the facet joint angles, as reported in the literature. The young and the aged models were simulated in frontal (2g, 8g, and 15g) and rear (3g, 7g, and 10g) impacts. The responses were compared using head and relative facet joint kinematics, and nominal intervertebral disc shear strain. In general, the aged models predicted higher deformations, although the head kinematics were similar for all models. In the frontal impact, the M5075YO model predicted hard tissue failure, attributed to the combined effect of the more anteriorly located head with age and higher neck length relative to the female model. In the rear impacts, the F0575YO model predicted higher relative facet joint shear compared to the F0526YO; whereas, in the male model, the relative facet joint kinematics predicted by the M5026YO and M5075YO were similar. This was attributed to the higher lordosis and facet angle in females compared to males. This finding agrees with epidemiological data reporting that females are more likely to sustain WAD in rear impacts compared to males and that injury risk increases with age. This study demonstrated that, although the increased lordosis and facet angle did not affect the head kinematics, changes at the tissue level were considerable and relatable to the epidemiology. Future work will investigate tissue damage and failure through the incorporation of aged material properties and muscle activation.